Penapisan Virtual Basis Data Senyawa Tanaman Afrodisiak Asal Family Rutaceae Sebagai Inhibitor α-Amylase - ADRIANI ADRIANI (Journal Syifa Sciences and Clinical Research, 2022)
The family Rutaceae has plants with worldwide aphrodisiac effects, but their activity as an antidiabetic has not been widely reported. This study aims to predict the -amylase activity of aphrodisiac plant compounds from the Rutaceae family based on virtual screening. The -amylase receptor (PDB ID: 1XD1) was prepared using Pymol while the ligand was prepared using Pyrx. Virtual screening using Autodoct vina in Pyrx with acarbose as a control drug. The results of virtual screening were analyzed using Discovery Studio software to get potential compounds. Prediction of a potential compound target protein using Swiss Prediction Target while pharmacokinetic analysis is based on The lipinski rule. The results showed that lunamarine had the highest inhibitory activity (-8.9 Kcal/mol) against -amylase receptors and was close to acarbose control (-9.7 Kcal/mol). Lunamarine complies with the Lipinski rule and has a high probability of target protein. The study concludes that compounds from aphrodisiac plants from the family Rutaceae have antidiabetic activity. Lunamarin has the highest activity as an -amylase inhibitor compared to other compounds.